A corpus-based investigation of the English translations of Mao Zedong’s speeches - Huang, Libo; Shi, Xinyu (Frontiers in Psychology, 2022)
This study adopts a corpus-based approach to examine the linguistic features manifested in the English translations of Mao Zedong’s speeches, taking Winston Churchill’s speeches (representative of normalized spoken texts) and the spoken texts in BNC Sampler (representative of original spoken texts) as the reference corpora. By investigating the macro- and micro-linguistic features, it is found that the translated Mao’s speeches (both direct and inverse translations) differ from normalized spoken texts as well as original spoken texts in three aspects: (i) macro-linguistic features, (ii) the use of personal pronouns, (iii) the use of modal verbs. In terms of macro-linguistic features, the average word length of the English translations is higher than that of normalized spoken texts and that of original spoken texts; the standardized type/token ratio and average sentence length of the English translations are higher than those of original spoken texts, but lower than those of normalized spoken texts. Meanwhile, in terms of the use of personal pronouns, the English translations of Mao’s speeches prefer the underuse of the first person singular pronoun I. Furthermore, as far as modal verbs are concerned, the English translations of Mao’s speeches prefer the overuse of must and should on the one hand, and the underuse of shall, could, may, and would on the other hand. Therefore, it can be said that the translated Mao’s speeches exhibit some particular linguistic features, which can not only be differentiated from normalized spoken texts, but also be distinguished from original spoken texts. They are in a middle position in relation to normalized spoken texts as well as original spoken texts. This in-betweenness not only exhibits Mao’s creative and idiosyncratic language use, but also reflects the influence of the language transfer from Chinese into English.